Risk factor analysis and nomogram development for steatorrhea in idiopathic chronic pancreatitis. Issue 5 (27th July 2022) - Liu, Yu; Yin, Xiao Yi; Wang, Dan; Dong, Zhi Qi; Hao, Lu; Chen, Cui; Wang, Teng; Zhang, Di; Ma, Jia Yi; Yang, Huai Yu; Li, Juan; Zhang, Ling Ling; et al.
Abstract : Objectives: Steatorrhea, a sign of severe pancreatic exocrine insufficiency (PEI), is related to consequences caused by pancreatitis. This study aimed to identify predictors and to construct a nomogram for steatorrhea in idiopathic chronic pancreatitis (ICP). Methods: ICP patients admitted to our hospital from January 2000 to December 2013 were enrolled in this retrospective–prospective cohort study and randomly assigned to the training and validation cohorts. The cumulative rate of steatorrhea was calculated. A Cox proportional hazard regression model was used to identify predictors for steatorrhea and construct the nomogram. Internal and external validation of the nomogram was then performed. Results: There were 1633 ICP patients enrolled, with a median follow‐up duration of 9.8 years and 20.8% (339/1633) of patients developed steatorrhea following onset of ICP. Steatorrhea was observed in 93, 115, and 133 patients at 1, 3, and 5 years following diagnosis of CP, with a cumulative rate of 6.5% (95% confidence interval [CI] 5.1%–7.9%), 8.0% (95% CI 6.2%–9.8%), and 9.3% (95% CI 6.6%–12.0%), respectively. Male sex (hazard ratio [HR] 2.479, P < 0.001), diabetes mellitus at/before diagnosis of ICP (HR 2.274, P = 0.003), and aged less than 18 years at onset of ICP (HR 0.095, P < 0.001) were identified risk factors for steatorrhea. Initial manifestations were associated with development of steatorrhea. The nomogram was proven to have good concordance indexes. Conclusions: We identified predictors and developed a nomogram for predicting steatorrhea in ICP. It was recommended that high‐risk populations be followed up closely, which might contribute to the early diagnosis and treatment of PEI. Abstract : Risk factors for predicting the development of steatorrhea in idiopathic chronic pancreatitis (ICP) based on a large idiopathic chronic pancreatitis (ICP) cohort included male sex, diabetes mellitus at/before diagnosis of ICP, aged <18 years at onset of ICP, and initial manifestations. A nomogram was constructed to predict the incidence of steatorrhea and screen high‐risk groups.